Checklist of the salps (Tunicata, Thaliacea) from the Western Caribbean Sea with a key for their identification and comments on other North Atlantic salps - Hereu, Clara María; Suárez-Morales, Eduardo (Zootaxa, 2012)
In waters of the Northwestern Atlantic pelagic tunicates may contribute significantly to the plankton biomass; however, theregional information on the salp fauna is scarce and limited to restricted sectors. In the Caribbean Sea (CS) and the Gulf ofMexico (GOM) the composition of the salpid fauna is still poorly known and this group remains among the less studiedzooplankton taxa in the Northwestern Tropical Atlantic. A revised checklist of the salp species recorded in the North At-lantic (NA, 0–40° N) is provided herein, including new information from the Western Caribbean. Zooplankton sampleswere collected during two cruises (March 2006, January 2007) within a depth range of 0–941 m. A total of 14 species wererecorded in our samples, including new records for the CS and GOM area (Cyclosalpa bakeri Ritter 1905), for the CS (Cy-closalpa affinis (Chamisso, 1819)), and for the Western Caribbean (Salpa maxima Forskål, 1774). The number of speciesof salps known from the CS and GOM rose to 18. A key for the identification of the species recorded in the region is provided. Studies on the ecological role of salps in several sectors of the NA are scarce and deserve further attention.